Pulmonary circulation biomarkers acquired by cardiovascular magnetic resonance in population after heart transplant. (8th February 2021) - Opatril, L; Panovsky, R; Machal, J; Mojica-Pisciotti, M; Holecek, T; Masarova, L; Feitova, V; Godava, J; Krejci, J; Zavodna, G; Spinarova, L
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This study was supported by the European Regional Development Fund - Project ENOCH. This study was conducted at Masaryk University as part of the project "New Methods in Diagnostic and Stratification of Cardiovascular Diseases" MUNI/A/1393/2019 with the support of the Specific University Research Grant, as provided by the Ministry of Education, Youth and Sports of the Czech Republic in 2019. Introduction   Right heart catheterization still remains the golden standard in measuring pulmonary circulation parameters, although its clinical use is limited due to it being an invasive examination. Pulmonary circulation biomarkers acquired by cardiovascular magnetic resonance (CMR) could provide a non-invasive alternative for assuming congestion in patients. Biomarkers such as pulmonary transit time (PTT), pulmonary transit beats (PTB) and pulmonary blood volume index (PBVI) are not new themselves, however, data on cut-off values of these biomarkers and on different populations are limited. To our knowledge, these biomarkers have never been measured in patients after heart transplant (HT) before and PTT from stress perfusion has only been acquired by a single study, which makes the data on this relatively new marker very limited.  Purpose   The purpose of this study was to calculate PTT stress/rest ratio and provide more evidence about pulmonary circulation biomarkers in HT patients.  Methods   In this retrospective study, 38 patients after HT who had undergone a CMR examination including contrast methods and stress CMR perfusion were enrolled. PTT values in both rest and stress perfusion were measured as peak-to-peak time in main contrast bolus of dual-bolus stress CMR examination. PTB was calculated by dividing PTT by RR interval obtained from heart rate and PBVI from PTB and right ventricle systolic volume. PTT under stress and rest condition was afterwards compared and PTT ratio was calculated dividing stress values by rest values. Obtained results were further compared to a healthy group as published previously. PTT ratio of HT patients was then compared to measurements conducted on a control group consisting of 10 patients after anthracycline treatment.  Results   Patients after HT showed biomarker values as follows: PBVI 250 ± 59 mL/m2, PTT 6, 26 ± 1, 05 s, PTT stress 5, 66 ± 1, 09 s, PTB 7, 39 ± 1, 31 and PTT ratio 0, 91 ± 0, 14. These results resemble previously published healthy group values (PBVI 308 ± 92 ml/m2, PTT 6, 8 s, PTB 7) and none of the patients enrolled in our study crossed the presented cut-off value of PBVI 492 mL/m2 for hemodynamic congestion. PTT ratio in our control group was 0, 77 ± 0, 14. In both the populations, PTT values under stress were lower than in rest condition and therefore PTT ratio values were below 1. Conclusions The study provided more evidence about pulmonary circulation biomarkers acquired by CMR in HT patients and presented PTT ratio as a new biomarker. Patients 1 year after HT have comparable values to those of healthy population. PTT stress values were shorter than PTT rest values in both HT group and control group.